2020
DOI: 10.1101/2020.06.25.169946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuroinvasion of SARS-CoV-2 in human and mouse brain

Abstract: Although COVID-19 is considered to be primarily a respiratory disease, SARS-CoV-2 affects multiple organ systems including the central nervous system (CNS). Reports indicate that 30-60% of patients with COVID-19 suffer from CNS symptoms. Yet, there is no consensus whether the virus can infect the brain, or what the consequences of infection are. Following SARS-CoV-2 infection of human brain organoids, clear evidence of infection was observed, with accompanying metabolic changes in the infected and neighboring … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
380
5
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(430 citation statements)
references
References 47 publications
22
380
5
8
Order By: Relevance
“…The neuroinvasion and neurotrophism by SARS-CoV-2 observed here is consistent with other pre-print studies, which include reports of infection of human neurons and astrocytes using monolayer and organoid approaches (Jacob et al, 2020;Ramani et al, 2020;Song et al, 2020), highlighting greater and productive infection in choroid plexus epithelial cells (Jacob et al, 2020) and less infection in NPCs (Ramani et al, 2020;Song et al, 2020). Consequences of neuronal infection include transcriptional dysregulation indicative of an inflammatory response (Jacob et al, 2020), missorted and phosphorylated Tau (Ramani et al, 2020), and increased cell death (Jacob et al, 2020;Ramani et al, 2020;Song et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The neuroinvasion and neurotrophism by SARS-CoV-2 observed here is consistent with other pre-print studies, which include reports of infection of human neurons and astrocytes using monolayer and organoid approaches (Jacob et al, 2020;Ramani et al, 2020;Song et al, 2020), highlighting greater and productive infection in choroid plexus epithelial cells (Jacob et al, 2020) and less infection in NPCs (Ramani et al, 2020;Song et al, 2020). Consequences of neuronal infection include transcriptional dysregulation indicative of an inflammatory response (Jacob et al, 2020), missorted and phosphorylated Tau (Ramani et al, 2020), and increased cell death (Jacob et al, 2020;Ramani et al, 2020;Song et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, this work tested the efficiency of Sofosbuvir, an FDA-approved brain-penetrant antiviral drug for positive-sense single-stranded RNA viruses ( 145 ), as a treatment for the SARS-CoV-2 infection and observed that this drug was able to rescue the altered synaptogenesis and decrease neuronal death and viral accumulation in these brain organoids ( 141 ). Song et al ( 117 ) also demonstrated that SARS-CoV-2 has neuroinvasive capacity in human brain organoids, particularly of NPCs and mature cortical neurons. Infected cells showed a hypermetabolic state and viral particles were accumulated within endoplasmic reticulum-like structures, indicating the virus ability to use the neural cell machinery to replicate ( 117 ).…”
Section: Brain Organoids As a Model Of Cns Infection By Sars-cov-2mentioning
confidence: 97%
“…Song et al ( 117 ) also demonstrated that SARS-CoV-2 has neuroinvasive capacity in human brain organoids, particularly of NPCs and mature cortical neurons. Infected cells showed a hypermetabolic state and viral particles were accumulated within endoplasmic reticulum-like structures, indicating the virus ability to use the neural cell machinery to replicate ( 117 ). In addition, a hypoxic environment and extensive neuronal cell death were observed in high density SARS-CoV-2 infected areas, suggesting that virus infection could promote death of nearby cells ( 117 ).…”
Section: Brain Organoids As a Model Of Cns Infection By Sars-cov-2mentioning
confidence: 97%
“…In a recent study, Song et al showed widespread expression of ACE2 protein in neurons and cells close to the lumen of the human brain organoids. They further showed SARS-CoV-2 can infect brain organoids, which can be blocked using ACE2 specific antibodies, or by administering cerebrospinal fluid from a COVID-19 patient, indicating the requirement of ACE2 for infection of brain organoids (Pavillet & Selvakumar, 2020;Song et al, 2020). Successful viral infection of brain tissue was also demonstrated in transgenic (Tg) mice expressing hACE2, following intranasal administration, which emphasized potentiality of olfactory route for SARS-CoV-2 entry in human brain (Pavillet & Selvakumar, 2020;Song et al, 2020).…”
Section: Neural Invasion By Other Betacoronaviruses Including Sars-mentioning
confidence: 98%
“…(and also TMPRSS2) in brain/neural tissue ( Figure 1). Any neuronal expression of ACE2 protein and SARS-CoV-2 infectivity was only shown in human pluripotent stem cells (PSCs)-derived mixed neurons, or human brain organoids, and not directly in human brain tissue (Bullen et al, 2020;Pavillet & Selvakumar, 2020;Song et al, 2020). In a recent study, Song et al showed widespread expression of ACE2 protein in neurons and cells close to the lumen of the human brain organoids.…”
Section: Neural Invasion By Other Betacoronaviruses Including Sars-mentioning
confidence: 99%